"Because all mothers is not the same": The development and implementation of an in loco parentis informed consent procedure to enroll adolescent girls and young women to participate in HIV research. (December 2021) - Bonner, Courtney Peasant; Fisher, Celia B.; Carney, Tara; Browne, Felicia A.; Gichane, Margaret W.; Howard, Brittni N.; Turner, Leslie; Wechsberg, Wendee M.
Abstract: Introduction: South Africa has one of the highest incidences of HIV among adolescent girls and young women (AGW), ages 15–24, and recent research has focused on developing interventions for HIV prevention. However, the South African National Health Act requires those under 18 years of age to obtain a guardian's permission to participate in research. Limiting research enrolment to AGYW who can obtain guardian consent may lead to non-representative findings. Therefore, innovative, inclusive consent approaches that protect AGYW from the risks of research are needed. Methods: This report details the development and implementation of an approach called the in loco parentis (in place of parent) consent procedure. In loco parentis consent provides a vehicle for adolescent participation that protects adolescents from potential social harms. The in loco parentis consent procedure does not seek to obtain independent minor consent but seeks to obtain permission for the minor to participate in research from a trusted adult who is not a minor's parent or legal guardian. This report also qualitatively explores the experiences of 31 AGYW who were recruited into a behavioral HIV prevention study using this method. Results: Findings suggest that the in loco parentis consent procedure is a feasible and acceptable method to inclusively AGYW in HIV research. Conclusions: The in loco parentis procedure may provide a more inclusive strategy to recruit AGYW for HIV research to increase the generalizability of findings.